O trabalho com as capacidades linguístico-discursivas no ensino médio: por um ensino de gramática mais reflexivo - Malaquias, Aline da Silva (2013)
After about sixteen years since the publication of Parâmetros Curriculares Nacionais, we can say that we are experiencing a transitional period in the teaching of Portuguese language marked mainly by theoretical and methodological contradiction with regard to the relationship between the classes of textual production, primarily from the perspective of genres of text and grammar lessons in a prism essentially theoretical and classificatory. We recognize and check that this contradiction has been reflected in the texts of the vestibular candidates, thereby this paper aims, firstly, to evaluate how the candidates are mobilizing linguistic aspects in the text considering the communicative situation and, secondly, it aims to prepare proposals for activities in a epilinguistic perspective that work the possible difficulties encountered in the analyzed texts. Therefore, the Applied Linguistic emerges as a magnified reflection about the teaching of language and society (MOITA LOPES, 2009), and Interactionism Socio discursive (ISD) as theoretical and methodological base that sets up the concept of language that underlies us to understand the role of linguistic knowledge mobilized in textual constitution and the text as communicative action of human (BRONCKART, 2006; SCHNEUWLY e DOLZ, 2004; CRISTOVAO, 2007; PEREIRA, 2009; among others). Considering this paper as qualitative, documentary, interpretative and explanatory research, we seek in twenty-two textual productions of Selection Process Series 2012 of the Federal University of Paraíba the representative corpus of our issue, observing variables of courses and proposals of writing to order to locate the analysis. In conclusion, we certificate that large number of candidates had difficulty articulating structures of subordination and we elaborated, among other activities, that some could be alternative to work them.